Assessment of the Linnaean type material of the Nose-horned viper, Vipera ammodytes (Linnaeus, 1758) - Krecsák, László; Bauer, Aaron M.; Westerström, Alexander; Wahlgren, Richard; Tomović, Ljiljana; Stille, Bo; Åhlander, Erik (Zootaxa, 2024)
Within the framework of surveys investigating the origins of Linnaean taxa, we assessed the evidence supporting historical taxonomic and nomenclatural proposals and decisions regarding the nose-horned viper (Vipera ammodytes). The viper was described as Coluber ammodytes Linnaeus, 1758 from “the Orient.” Bruno (1968) assessed the pre-Systema Naturae Ed. 10 sources and designated the specimen described in detail by Linnaeus as the lectotype of the species and restricted the type locality to near Castello Nuovo di Duino (Trieste, Venezia Giulia NW), NE Italy. We used a two-pronged approach using literary sources and statistical analyses to show that previous type locality restrictions suggested by different authors (including Bruno), were made incorrectly, without a proper assessment of the history or the morphological characteristics of the existing type material. Our surveys suggest that the lectotype was collected by the Swedish diplomat Edvard Carleson (1704–1767) in Belgrad Forest (Belgrad Ormanı), Belgrad village, Istanbul Metropolitan Municipality, Türkiye, between August 1738 and June 1746. In light of our results, the populations currently known as V. a. montandoni Boulenger, 1904 become the nominotypical subspecies, with the type locality Belgrad Forest (Belgrad Ormanı), Belgrad village, Istanbul Metropolitan Municipality, Türkiye. Nose-horned viper populations from the north-western and central parts of the distribution range of the species that were regarded as nominotypical, thus become Vipera ammodytes illyrica (Laurenti, 1768).